Pengembangan Aplikasi Mobile pada Studi Kasus Penjualan Sayur dan Buah Berbasis Android - Aries Saifudin; Abdul Wahid; Ismael Urzaiz Aranda; Sami Amruallah; Jonius Simanungkalit (CV. Multi Kreasi Media, 2024)
The high mobility of society and changing lifestyles have driven the adoption of online transactions in the world of commerce. In this context, mobile commerce applications have become a solution to provide various products, including fruits, vegetables, and other kitchen necessities, with easy search and payment processes. The development of such applications can be managed using the Scrum framework and visualization tools such as UML (Use Case and Activity Diagram) to improve efficiency and structure. Thus, mobile commerce applications offer a practical solution for people to fulfill their daily needs through digital platforms.